2020
DOI: 10.1111/jce.14774
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare utilization and cost in patients with atrial fibrillation and heart failure undergoing catheter ablation

Abstract: Background: Catheter ablation is an effective treatment for patients with atrial fibrillation (AF) and heart failure (HF). However, little is known about how healthcare utilization and cost change after ablation in this population. We sought to determine healthcare utilization and cost patterns among patients with AF and HF undergoing ablation. Methods: Using a large United States administrative database, we identified (n = 1568) treated with ablation with a primary and secondary diagnosis of AF and HF, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…18 In a more recent study, Friedman et al examined reductions in healthcare utilization among patients with PsAF undergoing CA (device agnostic) in the 12-month pre-versus post-ablation period. 19 The authors reported 64% reduction in AFrelated inpatient admissions, 59% reduction in ED visits, and 13% reduction in cardioversions in the 12-month post-versus pre-ablation period among PsAF patients. Our results align with those from Friedman et al, with significant reduction in healthcare utilization observed among patients with PsAF treated with STSF catheter in our study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…18 In a more recent study, Friedman et al examined reductions in healthcare utilization among patients with PsAF undergoing CA (device agnostic) in the 12-month pre-versus post-ablation period. 19 The authors reported 64% reduction in AFrelated inpatient admissions, 59% reduction in ED visits, and 13% reduction in cardioversions in the 12-month post-versus pre-ablation period among PsAF patients. Our results align with those from Friedman et al, with significant reduction in healthcare utilization observed among patients with PsAF treated with STSF catheter in our study.…”
Section: Discussionmentioning
confidence: 95%
“…Using a similar study design, Ladapo et al 18 found significant reductions in the number of outpatient appointments, inpatient days, and ED visits among continuously enrolled patients 6 months postablation compared to 6 months preablation. In a more recent study, Field et al 19 examined reductions in health care utilization among patients with PsAF undergoing CA (device agnostic) in the 12-month pre- vs postablation period. The authors reported 64% reduction in AF-related inpatient admissions, 59% reduction in ED visits, and 13% reduction in cardioversions in the 12-month post- vs preablation period among PsAF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Large evidence has shown that catheter ablation in patients with AF resulted in significant reductions in healthcare utilization and cost: using a large US administered database, it was found that catheter ablation, through 3 years of follow-up, restrained health care consumption mainly for AF-related admissions [ 14 , 29 ]. Among covariate-balanced cohorts, a significant reduction in healthcare costs was observed in AF patients who underwent catheter ablation versus those who did not, and this effect was mainly driven by hospitalization-related expenditures, both AF-related hospitalizations, and those for all other causes.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] Similar findings were reported by Field et al at 3-year follow-up in patients with AF and heart failure undergoing catheter ablation. [ 36 ] In two recently published studies, the authors showed benefits of catheter ablation in terms of healthcare utilisation and cost in both paroxysmal and persistent AF. [ 13 ],[ 23 ]…”
Section: Impact Of Catheter Ablation On Healthcare Utilisationmentioning
confidence: 99%